Diagnosis of secondary dysmyelopoiesis via costochondral rib aspirate in a dog. (November 2014) - Mathis, Justin C.; Yoo, Seung H.; Sullivan, Lauren A.
Abstract Objective To describe a novel bone marrow sampling technique utilized in a dog diagnosed with secondary dysmyelopoiesis. Case Summary A 1.5‐year‐old female spayed Lhasa Apso was treated for generalized seizures, aspiration pneumonia, and severe sepsis. Pertinent history included administration of phenobarbital (2.1 mg/kg PO q 12 h) for the 6 months prior to presentation for suspected idiopathic epilepsy. Initial leukopenia and thrombocytopenia was attributed to underlying sepsis and disseminated intravascular coagulation. Progressive decline in all cell lines (ie, leukopenia, thrombocytopenia, and anemia), along with history of phenobarbital administration, suggested myelodysplastic disease. Bone marrow cytology via serial costochondral rib aspirates confirmed secondary dysmyelopoiesis. Phenobarbital therapy was abruptly discontinued and replaced with alternative anticonvulsant therapy. Complete resolution of the observed leukopenia, thrombocytopenia, and anemia were observed 2 weeks after discontinuation of phenobarbital. New or Unique Information Provided Costochondral rib aspirate appears to be a simple, viable method for bone marrow evaluation in dogs. Dysmyelopoiesis is a rare adverse effect of phenobarbital administration that can possess fatal consequences if not quickly recognized. Prompt diagnosis and discontinuation of the inciting drug is imperative to successful case management. Prognosis for return of bone marrow function appears good following drug discontinuation.